2002
DOI: 10.1002/hipo.1103
|View full text |Cite
|
Sign up to set email alerts
|

Early induction of secretoneurin expression following kainic acid administration at convulsant doses in the rat and gerbil hippocampus

Abstract: The expression of secretogranin-II and its major proteolytic product secretoneurin (SN) is under the control of neuronal excitation, as demonstrated by treating rats with the excitotoxic kainic acid (KA). Differences in the structure and function of the hippocampus in rats and gerbils have been described; these suggest possible differential reactive responses to KA. In the present study, the SN immunostaining pattern in relation with cell damage is analyzed from 6 h to 4 days following KA administration in rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…It has been reported that neuronal COX-2 transgenic mice are more susceptible to kainic acid excitotoxicity [7]. This result is supported by previous studies that the extent of neuronal damage in gerbils induced by kainic acid was minor when compared with that of the rat [3,12]. In addition, differential expression patterns for caspases and transcription factor c-fos were recently described in the rat and gerbil, following systemic administration of kainic acid [3]: similar distribution pattern of caspase and c-fos was observed in kainic acid treated gerbils and rats although minimized in gerbils.…”
Section: Discussionsupporting
confidence: 74%
“…It has been reported that neuronal COX-2 transgenic mice are more susceptible to kainic acid excitotoxicity [7]. This result is supported by previous studies that the extent of neuronal damage in gerbils induced by kainic acid was minor when compared with that of the rat [3,12]. In addition, differential expression patterns for caspases and transcription factor c-fos were recently described in the rat and gerbil, following systemic administration of kainic acid [3]: similar distribution pattern of caspase and c-fos was observed in kainic acid treated gerbils and rats although minimized in gerbils.…”
Section: Discussionsupporting
confidence: 74%
“…In contrast to immediate-early gene expression, ProSN mRNA levels may better reflect specific changes in neuronal secretory activity associated with transmitter release and detect also those coupled to a decreased activity. amphetamine rat striatum +50% [81] phencyclidine rat prefrontal cortex increase [82] lithium differentiated PC12 +60% [83] haloperidol, clozapine rat striatum, raphe +290% [66] clozapine rat prefrontal cortex increase [84] citalopram rat zona inserta +50% [66] kainate rat hippocampus increase [85] kainate rat, gerbil hippocampus increase [86] kainate rat hippocampus +600% [87] kainate rat hippocampus +600% [88] reserpine rat adrenal medulla +150% [89] reserpine rat hypothalamus, brain stem +250% [90] histamine bovine chromaffin cells +400% [91] nicotine, prostaglandin E bovine chromaffin cells +330% [33,69] PACAP bovine chromaffin cells +60% [69,92] amphoterin (RAGE receptor agonist) mouse neuroblastoma cells +350% [93] hormones/trophic factors: estrogen male rat pituitary +155% [94] estrogen female rat hypothalamus +350% [95] adrenalectomy rat hypothalamus +380% [96] lactation rat hypothalamus +240% [96] ovariectomy female rat pituitary +300% [95,97] NGF rat PC12 cells +460% [98] bFGF human neuroblastoma cells +420% [99] EGF GH4 pituitary tumor cells +600% [100] interleukin 1 bovine chromaffin cells +230% [101] TNF-α bovine chromaffin cells +300% [101] hypoxia:…”
Section: Gene Expressionmentioning
confidence: 99%
“…Although several articles have reported a correlation between SN and neurological diseases including Alzheimer disease (3)(4)(5), Parkinson disease (8), and epilepsy (9,10), little literature has examined the role of SN in stroke (7). Human stroke is a leading cause of death and disability worldwide (11), and as yet there is no effective treatment that enhances stroke recovery.…”
Section: Introductionmentioning
confidence: 99%